Inorganic nanoparticle empowered biomaterial hybrids: Engineered payload release - Morillas-Becerill, Lucía; De Cola, Luisa; Zuidema, Jonathan M. (Frontiers in Nanotechnology, 2022)
There are many challenges in delivering active pharmaceutical ingredients from biomaterials, including retention of payload activity, accurate temporal release, and precise spatial administration, to name only a few. With our constantly increasing knowledge of biology and physiology, pathologies that require therapeutic interventions are becoming more understood. While the desired temporal and spatial administration of a therapy might be theorized, the ability to deliver an active therapeutic in a precise location during a specific time frame is often challenging. This has led researchers to develop hybrid biomaterials containing inorganic nanoparticles in order to combine the advantages of both inorganics and organics in payload delivery applications. Organic materials have many beneficial properties, including the ability to form networks and matrices to create three-dimensional structures from the nanometer to centimeter scale, biodegradability, the versatility to use both synthetic and natural precursors, and ease of chemical modifications, while inorganic materials offer highly controllable nanoscale features, can entrap and protect therapeutics, and have degradation properties that can be tightly regulated. Here in, we discuss the current state-of-the-art in active pharmaceutical ingredient delivery from biomaterial hybrids, demonstrate the added levels of control that these hybrid biomaterials offer, and give our perspective on future innovations in the field.